La strumentazione scientifica e la cultura: Vedere le arie attraverso il bagno pneumatico - Aquilini, Eleonora; Testoni, Antonio (Chimica nella Scuola, 2025)
The gaseous state is, from an educational point of view, a difficult state of matter to deal with and acquire. Studying gases presents considerable cognitive difficulties because their materiality is not perceived. In fact, while the solid and liquid states have always been consciously perceived and used by mankind, the gaseous state only began to exist recently, at the beginning of the eighteenth century (Hales, Black), although phenomena and experiments involving gases had been known since antiquity. The study of gases was made possible thanks to the pneumatic bath. Understanding the importance of this instrument for the birth of chemistry as a science has great cultural and educational value.